Analysis of Cooperative Defense System of Water Conservancy Network Security Based on Software Defined Security - XIAO Yaoxuan; MU Duo; QIN Zening; GUO Dongbao (Renmin Zhujiang)
In view of the increasingly concealed,complicated,and intelligent network attacks,this paper analyzes the security protection status and network security problems faced by the water conservancy network.A cooperative defense system of water conservancy network security is proposed,and a cooperative defense control system of network security is designed according to the system.On the basis of software defined security architecture,the control layer and security layer of traditional hardware or virtualized security devices are separated.The security resource pool provides security protection,and the security control platform is responsible for management and command delivery.Furthermore,security services can be arranged according to different protection requirements to construct multiple security protection mechanisms,so as to provide technical support for realizing the cooperative defense capability of water conservancy network security featuring internal and external cooperation and linkage between the upper and lower levels.